Analisis Akhlak Digital Siswa SMP dalam Buku Teks PAI: Pencegahan Ghibah, Fitnah, dan Ujaran Kebencian - Nadiva Gita Syamsiyah; Hindun Maulidana; Devy Habibi Muhammad (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2026)
This study examines junior high school students’ digital morality (digital akhlak) through an analysis of Islamic Education (PAI) textbooks, focusing on the prevention of ghibah, slander/misinformation, and hate speech. The study is grounded in the growing intensity of adolescents’ online interactions, which heightens ethical risks such as online backbiting, the spread of unverified information (hoax), and degrading expressions that may harm social cohesion. The study aims to describe how the textbook represents values and prohibitions related to these issues, to analyze instructional presentation (narratives, religious evidence, learning activities, and assessments), and to assess the alignment of textbook content with a digital morality framework that contextualizes Islamic moral values for online environments. Using a library research design and content analysis of the PAI textbook as the primary document, the discussion is strengthened by recent Indonesian journal literature on digital literacy, Islamic communication ethics, and moral education for digital natives. The findings indicate that the textbook provides a strong basis for preventing ghibah through clear definitions, scriptural reinforcement, and affective messages about safeguarding others’ dignity; it addresses slander/misinformation primarily through operational tabayyun skills, including source and content verification and contextual checking; meanwhile, the prevention of hate speech is present implicitly through prohibitions against insulting, mocking, and prejudging, yet requires more explicit enrichment via contextual cases and ethical response strategies for students as bystanders. Overall, the textbook has substantial potential to foster students’ digital morality when supported by consistent classroom habituation and contextual pedagogy.